A Missed Opportunity for U.S. Perinatal Human Immunodeficiency Virus Elimination: Pre-exposure Prophylaxis During Pregnancy. Issue 4 (October 2017) - Fruhauf, Timothee; Coleman, Jenell S.
Abstract : OBJECTIVE: To estimate the proportion of women at increased risk of sexual human immunodeficiency virus (HIV) acquisition during pregnancy in a high HIV incidence urban setting to identify those who may be eligible for pre-exposure prophylaxis. METHODS: We conducted a retrospective cohort study of women who received prenatal care at a large academic center in 2012. Univariable analyses and multiple logistic regression models were built to identify correlates for pre-exposure prophylaxis eligibility. RESULTS: Among 1, 637 pregnant women, mean age was 27.6 years (SD 6.3), 59.7% were African American, and 56.0% were single. Based on the Centers for Disease Control and Prevention's guidelines, more than 10% of women were at increased risk for HIV acquisition during pregnancy and eligible for pre-exposure prophylaxis. Younger [adjusted odds ratio (OR) 0.9/1-year increase, 95% CI 0.8–0.9], single (adjusted OR 2.4, 95% CI 1.2–4.8), African American women (adjusted OR 3.3, 95% CI 1.6–6.7) with higher parity (adjusted OR 1.3/one-child increase, 95% CI 1.1–1.5), and who smoked regularly during pregnancy (adjusted OR 1.8, 95% CI 1.0–3.0) had greater odds of being eligible for pre-exposure prophylaxis at any time during pregnancy. CONCLUSIONS: Pregnancy is a vulnerable period during which some heterosexual women in urban settings have a high risk for HIV acquisition and stand to benefit from pre-exposure prophylaxis. Abstract : A large proportion of pregnant women at high risk for human immunodeficiency virus acquisition are eligible for pre-exposure prophylaxis.